Health selection and the effect of smoking on mortality - Jérôme Adda; Valerie Lechene (Institute for the Study of Labor (IZA), 2011)
We show that individuals who are in poorer health, independently from smoking, are more likely to start smoking and to smoke more cigarettes than those with better non-smoking health. We present evidence of selection, relying on extensive data on morbidity and mortality. We show that health based selection into smoking has increased over the last fifty years with knowledge of its health effects. We show that the effect of smoking on mortality is higher for high educated individuals and for individuals in good non-smoking health.
urn:nbn:de:101:1-201201107556
Keywords: I12; 330; life expectancy; tobacco; confounding; Rauchen; Gesundheitsvorsorge; Sterblichkeit; Schätzung; Schweden